DEVELOPMENT AND VALIDATION OF AN INSTRUMENT TO MEASURE NURSING HOME WORK ENVIRONMENT FOR NURSES. (11th November 2018) - Cho, E; Min, D; Lee, K; Kim, J; Chang, S; Kim, H; Kim, S
Abstract: A work environment that supports professional nursing practice is important for quality of care, resident safety, and job satisfaction of RNs, who need greater participation in decision-making to deliver quality of care in nursing homes. Most of the previous studies used the Practice Environment Scale of the Nursing Work Index, originally developed to measure work environment in a hospital setting. This study aimed to develop and test the validity and reliability of an instrument measuring nursing home work environment. The process of instrument development was conducted in the following three phases: Development of the initial questionnaire, Content validation and pilot testing, and Validity and reliability testing. Exploratory and confirmatory factor analyses were conducted using STATA 13.1. Survey data were collected from 184 nurses in 62 nursing homes in South Korea. The final model derived from factor analysis yielded a 27-tiem of five factors; "Nurse participation in nursing home affairs, " "Well-defined professional roles and responsibilities, " "'Nurse manager ability, leadership, and support of nurses', " "Staffing and resource adequacy, " and "Communication and coordination." For all five factors, values of RMSEA varied from 0.00 to 0.077, CFI from 0.96–1.00, and TLI from 0.93–1.01. The Cronbach's alpha estimate was .93 for the whole 27-item nursing home work environment scale and that of subscales ranged from 0.77 to 0.88. Therefore, the selected items were considered to be suitable for measuring the nursing work environment of nursing homes in South Korea through organizational characteristics of nursing homes and characteristics of patients and nursing activities.